Studi Literatur : Peran Komik Digital Berbasis Konteks Terhadap Pembelajaran Bahasa Inggris Siswa Sekolah Dasar - Saly Kurnia Octaviani; Arumsari; Rahmatika (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the role of context-based digital comics in English language learning for elementary school students through a systematic literature review. Data were collected from Google Scholar and ERIC databases, limited to publications from 2020 to 2026. Following a PRISMA-guided selection process, 18 articles were selected for thematic analysis and narrative synthesis. The findings reveal that context-based digital comics significantly contribute to three dimensions of English learning: vocabulary acquisition, where visual and narrative context helps students infer and retain word meanings; reading comprehension and grammar mastery, where visual elements reduce cognitive load and support contextual inference; and motivation and learner engagement, where the interactive nature of digital comics encourages voluntary language practice. This study recommends structured integration of context-based digital comics into elementary English curricula, supported by adequate teacher training.